Erosion of Penitentes Under Experimental Conditions Relevant to Ice‐Covered Airless Worlds. Issue 10 (20th October 2021) - Berisford, D. F.; Foster, J. T.; Kosberg, J. A.; Furst, B. I.; Poston, M. J.; Daimaru, T.; Lang, M.; Backman, L.; Macias, A.; Hand, K. P.
Abstract: The submeter‐scale surface morphology of ice‐covered worlds is poorly constrained by observations, but is important for understanding their physics and chemistry. In this experiment, we exposed preformed snow structures to temperature, pressure, and solar irradiance conditions similar to those on Europa and Enceladus. The sample consisted of 2‐D sinusoidal penitente‐like ridges, 2.5 cm tall with 1.25 cm spacing. Over 1 month at 165–175 K, and 10 −4 Pa, the ridges decreased in height by 20% and became more triangular and less sinusoidal, evolving toward a more flat surface. This despite the fact that the troughs appear brighter than the peaks, indicating focusing of light into the troughs. This suggests that penitentes are unlikely to be stable on airless worlds with free‐molecular flow conditions, which is significant for understanding the spectral and thermal properties of these worlds, and for understanding risks for future landed spacecraft. Plain Language Summary: Ice penitentes are blade‐like ice or snow structures formed by sublimation and heating from the Sun, often seen at high altitudes on Earth's subtropical mountains, particularly the Andes. A key question is whether they can arise in vacuum, on worlds without an atmosphere such as Europa and Enceladus. This is important for understanding the physics of these worlds, as well as for understanding the terrain for future landed spacecraft. We have no high‐resolution images of these worlds to tell if such structures exist, so we use laboratory experiments to simulate these icy surfaces. In our experiment, we start with a preformed set of 2.5 cm tall penitente‐like ridges, formed using a plastic mold filled with snow. Inside a vacuum chamber, a solar‐like light source illuminated the penitentes for 60 days. During the first 2 weeks of the experiment, we kept ice temperatures between −138°C and −113°C, and we saw no changes. During the second half of the test, we raised temperatures to −98°C to −108°C. The penitentes shrank in height by 20%, and become more triangular in shape. This is an indication, consistent with model predictions, that penitentes need an atmosphere to grow, and we may not expect them on Europa and Enceladus. Key Points: This is the first ice penitente experiment under hard vacuum (free‐molecular) conditions Preformed penitentes undergo sublimation erosion, evolving toward a flat morphology, during simulated solar irradiance Peaks are warmer than troughs, consistent with diminishing peak heights, despite visibly brighter troughs indicating focusing of light